Populasi dan Keanekaragaman Hewan Makrobenthos Pada Perairan Tertutup dan Terbuka Di Teluk Awur, Jepara [Macro Benthic Animal Population and Biodiversity In Closed And Open Waters In The Awur Bay, Jepara] - Ruswahyuni Ruswahyuni (Faculty of Fisheries and Marine Universitas Airlangga, 2010)
AbstractAwur Bay waters is an area that has different water conditions, namely closed and open waters. Open water is an aquatic area facing the open sea without any barrier, island and the mainland either in front or in the form of open sea, so that open water is strongly influenced by waves and tides. Consequently in these waters, the waves interaction ,stream will cause turbulence. While the closed waters is impeded by inland waters or in the form of the bay therefore stream and wave power will reduce when it arrived at the beach. Macrobenthic animals are aquatic organisms that live in the bottom sediments, whether on top or in the bottom of sediments. Population is a group of individuals and the same species in a place and time, while indicating the presence of species diversity in ecosystems. The aims of the study is to analyze the difference effects of closed and open waters in the Awur bay Jepara, on the population and diversity of macrobenthic animals based on differences in the characteristics of the waters.